Picture Exchange Communication System (PECS) Malay Application for Global Development Delay (GDD) and Autisme Spectrum Delay (ASD) Kids - Kamoruddin, Noor Syafawati; Sudin, Nor'aisah (Evolution in Electrical and Electronic Engineering, 2024)
Most of the Global Development Delay (GDD) and Autism Spectrum Disorder (ASD) kids are facing speech delay problem and cannot communicate well around with people. With the help of Picture Exchange Communication (PECS) and mobile application approach, this method will help the caregivers and therapist to assist the special need kids in understanding and learning the surrounding objects and verbs. PECS Malay Application focuses on teaching and facilitating communication in Malay Language from GDD and ASD children. This project is developed using PHP MySQL for the whole web system and Kodular for the Android application. The apps also integrate with the database to record the childrens’ progress, which can be helpful for tracking and monitoring their development over time. Based on the result obtained from the apps testing and verification conducted in Pusat Pemulihan Dalam Komuniti (PPDK) Parit Raja and Program Pendidikan Khas Integrasi Sekolah Kebangsaan Parit Raja, it indicates that this account for approximately 85.71% of the candidates successfully achieved the highest score in the exercise/activity. This is shown that PECS Malay App was effective in supporting their leaning and this app can provide valuable assistance in improving their communication skills and understanding of objects and actions. Additionally, the survey conducted among user’s representative of this PECS Malay App provide valuable insights and feedback which helps in improving the features, functionality and overall user experience of the app. By incorporating suggested improvements ad addressing specific requests, this can ensure that the app becomes a more comprehensive and satisfying communications and therapy tools for children with special needs.